2019
DOI: 10.2139/ssrn.3383936
|View full text |Cite
|
Sign up to set email alerts
|

Employment and Performance Effects of Circular Economy Innovations

Abstract: Circular economy (CE) describes an economic concept that aims at saving resources by minimizing the use of material and energy over the entire life-cycle or products, including repair, reuse and recycling. CE innovations help to realize the goals of a sustainable development and target both the environmental, economic and social dimensions of sustainability. This paper looks at the economic and social dimensions by investigating the performance and employment effects of CE innovations at the firm level. CE inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The employment opportunities derived from the application of the CE are one of the most important topics for the future of students (Horbach et al, 2015;Morgan and Mitchell, 2015). However, only one group included it in a proposal: "entrepreneurs who are dedicated to the repair of devices and work against planned obsolescence".…”
Section: Teacher Training In a Higher Educationmentioning
confidence: 99%
“…The employment opportunities derived from the application of the CE are one of the most important topics for the future of students (Horbach et al, 2015;Morgan and Mitchell, 2015). However, only one group included it in a proposal: "entrepreneurs who are dedicated to the repair of devices and work against planned obsolescence".…”
Section: Teacher Training In a Higher Educationmentioning
confidence: 99%
“…Like the CE itself, CE employment has been defined in many different ways (Horbach et al, 2015;Van Oort et al, 2018). Following the focus on sustainability in public policy, many studies tend to define and label CE jobs as "green jobs" (Horbach et al, 2015) or jobs that contribute substantially to preserving or restoring environmental quality (UNEP, 2008, p. 3).…”
Section: Defining Employment In the Cementioning
confidence: 99%
“…Most studies that have addressed CE employment focus either on estimating how many workers are active in the CE (e. or on calculating the net employment effect of the development of the CE, recognizing that the development of the CE may also crowd out or replace traditional industries. This body of literature has found that CE employment in Western nations typically accounts for between 0.5% and 5% of national employment (Horbach et al, 2015). 1 However, these figures might underestimate the true size of the CE because most studies focus on the 'green' component of the CE only and neglect the non-green jobs that enable the development of the CE (Van Oort et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations